Analysis of Lexical Collocational Errors in Essays Committed by Double-majored Students at Hanoi National University of Education = Phân tích lỗi sai trong cách kết hợp từ vựng ở bài viết luận của sinh viên ngành ghép ở Trường Đại học Sư phạm Hà Nội - Nguyen, Thi Thanh Huyen (Đại học Quốc gia Hà Nội, 2020)
This study is to classify main types of lexical collocational errors and identifying the possible causes of those errors in 63 essays by third-year double-majored students at Hanoi National University of Education (HNUE) based on the taxonomy proposed by Benson et al. (1997) and Richards (1973). It was found that Type 1 (verb + noun) in lexical collocational errors occurred most frequently in the participants’ writings and the lexical collocational errors were mainly due to the interlingual interference of Vietnamese. Some pedagogical implications are presented to alleviate those errors.